Teachers’ Perceptions on Global Competence: Investigating its Basic Dimensions - Zoe, Dr Karanikola (International Journal of Scientific Research and Management (IJSRM), 2022)
In the contemporary context of globalization and of intense demographic, economic, technological and social changes, formal education is called upon to redefine its multidimensional role and prepare future citizens for the global challenges of the 21st century. In such a context, the present study aims to investigate the extent to which teachers have developed global competence by exploring three key dimensions of global competence: knowledge and understanding, skills, attitude and values. The quantitative methodology was followed and the questionnaire tool was selected. Random sampling technique was used, and the questionnaire was delivered through google forms. The sample consisted of 350 active teachers who taught in public schools of primary and secondary education in the region of western Greece in the school year 2021-2022. Research findings show that the average value for the dimension of Knowledge and understanding is 3.62 (a lot), for the dimension of Skills is 3.37 (enough) and for the dimension of Attitude and values ​​is 3.93 (a lot). In addition, the control of the Pearson correlation coefficient of the nine factors for global competence shows a statistically significant positive correlation between them. Finally, gender, level of education, employment relationship and years of service seem to affect the results of the scale.